Identification of fine structure formation in high-speed ssteel after various heat treatment methods - Azimova, Lala; V.F. Gahramanov; S.N. Suleymanov; I.H. Hamdullaeva (My University, 2025)
Long-term preservation of the cutting ability of the blades of cutters made of cutting tools steels is one of the main requriments for them. The very thin cutting edge of the tool is blunted and corroded due to the high specific pressure during the cuttung process. During this process, a certain part of the mechanical work spent on separating the sawdust from the product by the cutter is converted into heat.
Keywords: Heat treatment; Quencing; Tempering; Cutting tools